Host Response to Coccidioides Infection: Fungal Immunity - Anh L. Diep; Katrina K. Hoyer; Katrina K. Hoyer; Katrina K. Hoyer (Frontiers in Cellular and Infection Microbiology, 2020)
Coccidioidomycosis is a fungal, respiratory disease caused by Coccidioides immitis and Coccidioides posadasii. This emerging infectious disease ranges from asymptomatic to pulmonary disease and disseminated infection. Most infections are cleared with little to no medical intervention whereas chronic disease often requires life-long medication with severe impairment in quality of life. It is unclear what differentiates hosts immunity resulting in disease resolution versus chronic infection. Current understanding in mycology-immunology suggests that chronic infection could be due to maladaptive immune responses. Immunosuppressed patients develop more severe disease and mouse studies show adaptive Th1 and Th17 responses are required for clearance. This is supported by heightened immunosuppressive regulatory responses and lowered anti-fungal T helper responses in chronic Coccidioides patients. Diagnosis and prognosis is difficult as symptoms are broad and overlapping with community acquired pneumonia, often resulting in misdiagnosis and delayed treatment. Furthermore, we lack clear biomarkers of disease severity which could aid prognosis for more effective healthcare. As the endemic region grows and population increases in endemic areas, the need to understand Coccidioides infection is becoming urgent. There is a growing effort to identify fungal virulence factors and host immune components that influence fungal immunity and relate these to patient disease outcome and treatment. This review compiles the known immune responses to Coccidioides spp. infection and various related fungal pathogens to provide speculation on Coccidioides immunity.